(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Undoubtedly, Federico García Lorca is one of the most prominent names in the history of literature. But he must also be recognized for his musical side, as he was a very good piano player. He met the most important Spanish composers in his days and really loved the flamenco and traditional music. He found songbooks from very different periods and even used numerous songs in his plays and productions with La Barraca. The main topic in this article is going to be his role as an investigator, because he conducted numerous studies in his travels in Granada, his province, Spain and America. And it is focused on his recording from 1931, Spanish folksongs, made in conjunction with the dancer and singer La Argentinita.